Studi Tentang Pakaian Sehari-hari Suku Anak Dalam di Desa Sungai Jernih Kecamatan Muara Tabir Kabupaten Tebo Provinsi Jambi - Pujianti, Pujianti; Ramainas, Ramainas; Ernawati, Ernawati (Journal of Home Economics and Tourism, 2013)
This study aimed to obtain information on everyday clothing Suku Anak Dalam in Sungai Jernih Village Muara Tabir sub-district Tebo regency Jambi province which includes the characteristics of everyday clothing and how to wear clothes everyday (apparel, school apparel, clothing outlets, hunting clothing and gardening clothes). The results of this study everyday clothing Suku Anak Dalam in the Sungai Jernih Village Muara Tabir subdistrict Tebo regency Jambi province the characteristics of clothing at home, gardening and hunting clothes for men are same wearing loincloths for women's clothing in an adult only home wearing gloves from the waist down limit, while still a girl wearing a tank top and sarong. school clothes (a children's) are wearing red and white uniforms like elementary school children in general. Clothes for shopping to the market of men and women is same with clothing at home if the wears top clothes as the general public. How to use everyday clothes that women are ridden by entering a sarong until limit the waist, then develop a fabric wrap to the next part gets left waist, used the materials. How to wear a tank top with the Java, wrapped around the upper body by wrapping cloth used is a long cloth. How to use loincloths for men that is in principle only wrapped around the waist. Â  Keywords: Everyday Clothes, Suku Anak Dalam